Assessment of food security in Kazakhstan in conditions of crisis Covid 19 - Zh. Zh. Yeszhanova; D. D. Yermekbayeva; U. A. Myrzayeva (Экономика: стратегия и практика, 2021)
In the article, the authors analyzed the changes in the main components of food security in Kazakhstan for 2020 to clarify the question of how the crisis associated with the Covid 19 coronavirus pandemic affected its level. The authors analyzed the main components of food security: they assessed the dynamics of changes in the physical and economic accessibility of food in the country, the quality and safety of products, sustainability and availability of resources, and also compared them with the average value of these criteria for 113 countries. A comparative analysis showed that the level of food security in our country exceeds the average level for the compared countries, and during the quarantine period Kazakhstan managed to increase these indicators, which indicates the effectiveness of the government measures taken to support the development of agricultural producers to ensure uninterrupted food delivery.